CREATING A MOTIVATIONAL ENVIRONMENT FOR THE PROFESSIONAL GROWTH OF RESTAURANT EMPLOYEES - Постова, Валентина; Рябенька, Марина (SWorldJournal, 2025)
The article presents a detailed overview of the key elements of an effective motivation system, such as: a clear vision of the company, an individual approach to each employee, systematic training and development, career growth, financial and non-material